Bauxite residue sinter leach process – phases formation, reaction pathways and kinetics - Hodge, Harrison; Rowles, Matthew; Hayes, Peter C; Hawker, William; Vaughan, James (2019)
Reactive silica in bauxite is a key challenge for the alumina industry due to the associated losses of sodium hydroxide and alumina associated with processing this impurity. The bauxite residue sinter leach process (BRSLP) is a potential method of recovering sodium hydroxide and alumina from bauxite residue. In this research, bauxite residue lime sinters were characterised using a combination of quantitative X-ray diffraction in conjunction with scanning electron microscopy as well as for leaching performance. It is shown that sintering reactions proceed at a significantly faster rate than previously reported which has a positive implication for industrial application. A new set of reactions and reaction pathways are proposed which describe bauxite residue lime sintering in greater detail than previously possible.